Effect of chicken manure biochar incorporated with potassium to the growth, yield and eating quality of glutinous maize planted on Silabukan Soil - Sierra Julius (Universiti Malaysia Sabah, 2017)
This study was carried out at Faculty of Sustainable Agriculture, Universiti Malaysia Sabah (UMS) Sandakan campus from April to September 2016 to determine the effect of chicken manure biochar (20 tonnes ha-1, 40 tonnes ha-1 and 60 tonnes ha-1) incorporated with potassium (90:60:60 kg ha-1, 90:60:90 kg ha-1 and 90:60:120 kg ha-1) on the growth, yield and eating quality of glutinous maize planted on Silabukan soil. The best rate of potassium and chicken manure biochar for yellow reddish glutinous maize was determined. The treatments that were involved in this experiment were control, three different rates of chicken manure biochar and three different rates of potassium fertilizer. For control treatment, NPK rate of 90:60:60 were applied without incorporating with chicken manure biochar. These treatments were arranged using completely randomized design (CRD) with three replications. The data collected were analysed using one-way ANOVA at 5% significant level. For vegetative growth results, treatment P3M2 (potassium 120 kg ha-1, chicken manure biochar 40 tonnes ha-1) gave the tallest maize (303.73 cm). Treatment P1M2 (potassium 60 kg ha-1, chicken manure biochar 40 tonnes ha-1) and treatment P3Ml (potassium 120 kg ha-1, chicken manure biochar 20 tonnes ha-1) produced the highest number of leaves (13). Treatment P2M3 (potassium 90 kg ha-1, chicken manure biochar 60 tonnes ha-1) gave the longest maize girth circumference (7.1 cm) and also recorded the highest first cob height from the soil surface (158.13 cm). For yield components results, treatment P2M2 (potassium 90 kg ha-1, chicken manure biochar 40 tonnes ha-1) had the longest mean length of cob (13.4 cm) while treatment P2M3 (potassium 90 kg ha-1, chicken manure biochar 60 tonnes ha-1) recorded the highest mean fresh weight of cob (75.426 g). For diameter and circumference of cob (cm), treatment P3M2 (potassium 120 kg ha-1, chicken manure biochar 40 tonnes ha-1) had the highest mean (2.2 cm) and (6.91 cm) respectively. Treatment P2M3 (potassium 90 kg ha-1, chicken manure biochar 60 tonnes ha-1) had the highest mean number of grains which (186.33) grains while treatment P2Ml (potassium 90 kg ha-1, chicken manure biochar 20 tonnes ha-1) showed the highest mean weight of 100 grains (14.66 g). For the total soluble solid content, treatment P1M2 (potassium 60 kg ha-1, chicken manure biochar 40 tonnes ha- 1) had the highest mean brix reading (16.966 %). For soil analysis test, treatment P1M3 (potassium 60 kg ha-1, chicken manure biochar 60 tonnes ha-1) showed the highest pH value (6.04), compared to the initial value (4.07). For nitrogen test, treatment P2M3 (potassium 90 kg ha-1, chicken manure biochar 60 tonnes ha-1) had increased the nitrogen content of Silabukan soil from 2.1% to 2.26% while treatment P3M2 (potassium 120 kg ha-1, chicken manure biochar 40 tonnes ha-1) had increased the phosphorus content from 0.105 ppm to 1.912 ppm. For fresh cob extrapolated yield and root dry matter content, treatment P2M3 (potassium 90 kg ha-1, chicken manure biochar 60 tonnes ha-1) produced 6.44 tonnes ha-1 and 14.66 g respectively. Therefore, the best treatment that can be recommended to the farmers is P2M3 (potassium 90 kg ha-1, chicken manure biochar 60 tonnes ha-1) as it produced more grains and had the highest mean fresh weight of cob, highest nitrogen content and had pH of 5.99 and also had the highest fresh cob extrapolated yield.